Suppressing Phosphorylated Focal Adhesion Kinase in Human Colorectal Cancer with Anti-Cancer Lead Compound - Ong, Hien Thi My; Jung, Jaeyong; Sung, Jeong Soo; Ates, Eda; Pyun, Jae-Chul; Kang, Min-Jung (KSBMB International Conference 2024: Abstract Book, 2024)
Colorectal cancer (CRC) stands as a prominent cause of global mortality, marked by numerous metastases and bleak prognoses. Chemotherapy resistance in CRC poses a formidable challenge, often resulting in treatment failure. This study endeavors to identify natural compounds with potential against CRC and elucidate their mechanisms of action as anticancer agents. Screening involved assessing the cytotoxicity of 37 natural compounds on colon cancer using the HCT116 cell line. Conferone emerged as the lead candidate, subsequently evaluated for its anti-migratory and anti-invasive effects on three colon cancer cell lines: HCT116, SW1116, and Colon205. Analysis revealed conferone's suppression of colon cancer cell proliferation without inducing normal cell death in CCD18Co cells. Treatment with conferone at 10 ？M led to decreased levels of focal adhesion kinase (FAK) and phosphorylated FAK (p-FAK) proteins. Molecular docking analysis demonstrated conferone's superior binding affinity compared to the established FAK inhibitor, 1,2,4,5-Benzene tetramine tetrahydrochloride, with shared amino acid binding sites. Notably, inhibition of FAK by conferone correlated with reduced cancer cell migration and invasion. Furthermore, FAK inhibition contributed to the downregulation of c-Myc, thereby hindering the glutaminolysis pathway crucial for cancer cell proliferation. These findings unveil conferone as a promising therapeutic agent targeting FAK, thereby altering cancer cell metabolic reprogramming and impeding colon cancer progression.